Strategi Penyusunan Kerangka Berpikir: Meningkatkan Kualitas Penelitian - Listiana, Heni; Anam, Khoirul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
A conceptual framework is a fundamental element in scientific research, serving as a guide to understanding the relationships between concepts and variables. This study explores various perspectives on conceptual frameworks, including definitions from experts, types of conceptual frameworks, and methods for their formulation. Several commonly used types of conceptual frameworks include deductive, inductive, conceptual, theoretical, and empirical frameworks, each with distinct characteristics and approaches. Additionally, this study outlines systematic steps in constructing a conceptual framework, starting from problem identification and literature review to the development of a conceptual model. A thorough understanding of conceptual frameworks enables researchers to conduct more structured analyses and produce valid findings that contribute to the advancement of knowledge. Thus, a well-developed conceptual framework plays a crucial role in ensuring the quality and coherence of scientific research.